Gene therapy methods (Academic Press, 2002)
This volume in the prestigious "Methods in Enzymology" series discusses methods currently used in preclinical and clinical gene therapy. Subjects covered in this book, such as the use of adeno-associated virus delivery for treatment of Parkinson's disease, are topical and are presented in the methods-oriented style popularized by this series.